2018
DOI: 10.15689/ap.2018.1704.8.08
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a Brazilian depression self-report measure (EBADEP): Original and short versions

Abstract: The present study aimed to investigate the diagnostic accuracy of a scale for the assessment of depressive symptoms, the EBADEP-A, and its short version. Also, we propose the application of the concept of equivalence to compare the discriminative capacity between the two scales, i.e., to determine whether a new procedure (i.e., EBADEP-A short version) is not worse than the procedure in use (i.e., the EBADEP-A). Participants were 80 individuals, 40 with a diagnostic of major depressive disorder based on SCID-I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 24 publications
1
9
0
5
Order By: Relevance
“…Moreover, the results suggest that the screening version, with a smaller number of items, has a capacity similar to the full version of EBADEP-A. This finding is in line with what was observed by Baptista and Carvalho (2018), who also found equivalence between the versions. The results of the diagnostic accuracy indicators, in general, also suggest the use of the screening version as this version obtained similar results to the full version, using fewer items and requiring less administration time.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Moreover, the results suggest that the screening version, with a smaller number of items, has a capacity similar to the full version of EBADEP-A. This finding is in line with what was observed by Baptista and Carvalho (2018), who also found equivalence between the versions. The results of the diagnostic accuracy indicators, in general, also suggest the use of the screening version as this version obtained similar results to the full version, using fewer items and requiring less administration time.…”
Section: Discussionsupporting
confidence: 89%
“…A rating scale is used to measure if the participant agrees more with the first statement, the second, or with both at the same magnitude. Studies have revealed good psychometric properties for the scale (Baptista, 2012;Baptista & Carvalho, 2018;Bighetti et al, 2014).…”
Section: Baptista Depression Scale Adult Version (Ebadep-a; Baptista2012)mentioning
confidence: 99%
See 3 more Smart Citations